Implementasi Pendidikan Inklusif Pada Lembaga Pendidikan Anak Usia Dini Di Indonesia - Sakti, Syahria Anggita (Jurnal Golden Age, 2020)
Â AbstractThis study aims to analyze the extent of the implementation of inclusive education in early childhood education institutions in Indonesia. Inclusive education at an early age begins by accommodating the needs of children, identifying the special needs of children, and mapping the development potential and barriers of children now and in the future. Inclusive education provides opportunities for children with special needs to get an equal education. The practice of the inclusive education system implemented at the level of early childhood education still leaves problems, the implementation of inclusive education which is apparently still not inclusive. The issue of educators, supporting facilities, and inclusive education curricula in early childhood education institutions is also not yet capable Inclusive education in Indonesia must involve parents, teachers and the environment, the implementation of inclusive education in Indonesia leads to the goal of inclusive learning that provides the broadest opportunities- breadth to all children including children with special needs to get proper education in accordance with their needs.Keywords: Inclusive Education, Early Childhood Education, Education.Â AbstrakPenelitian ini bertujuan untuk menganalisis sejauh mana implementasi pendidikan inklusi pada lembaga pendidikan anak usia dini di Indonesia. Pendidikan inklusi pada anak usia dini dimulai dengan mengakomodasi kebutuhan anak, mengidentifikasi kebutuhan khusus anak, serta memetakan potensi perkembangan dan hambatan anak saat ini maupun di masa depan. Pendidikan inklusif senantiasa mengedepankan aspek kesetaraan bagi anak berkebutuhan khusus untuk memperoleh layanan pendidikan. Praktek sistem pendidikan inklusif yang di implementasikan pada tingkatan pendidikan anak usia dini masih menyisakan persoalan, yakni pelaksanaan pendidikan inklusif yang ternyata masih tidak inklusif. Persoalan tenaga pendidik, sarana prasarana pendukung, serta kurikulum pendidikan inklusif pada lembaga pendidikan anak usia dini juga belum mumpuni. Pendidikan inklusi di Indonesia harus melibatkan orang tua, guru dan lingkungan pembelajaran. Implementasi pendidikan inklusif di Indonesia senantiasa berpedoman pada tujuan pembelajaran inklusi yakni memberikan akses agar peserta didik anak berkebutuhan khusus memperoleh layanan pendidikan yang maksimal sesuai dengan kebutuhannya